2006
DOI: 10.1111/j.1475-1313.2006.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

End‐box scoring artefact evaluation of the Farnsworth‐Munsell 100‐Hue colour vision test

Abstract: The scoring artefact in the Farnsworth-Munsell 100-Hue test, arising from the grouping of the caps into four boxes, was investigated. The traditional method of scoring performed with the numbers of the anchor caps disregarded and the alternative scoring performed with the numbers of the anchor caps employed, were compared. For the traditional method of scoring, we revealed an increase of the error score of the outside (end-box) caps when the total error score was above 240. On the contrary for scoring performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For example, if the caps were ordered 3‐4‐5‐6, the TES would be zero, but if the numbers were ordered 3‐5‐4‐6, the TES would be 4. Several researchers have shown that using the traditional scoring method produces some error since the end caps are fixed, however when TES scores are less than 240, corrections have little to no benefit 21. In addition to TES, a radial plot can be created for each test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, if the caps were ordered 3‐4‐5‐6, the TES would be zero, but if the numbers were ordered 3‐5‐4‐6, the TES would be 4. Several researchers have shown that using the traditional scoring method produces some error since the end caps are fixed, however when TES scores are less than 240, corrections have little to no benefit 21. In addition to TES, a radial plot can be created for each test.…”
Section: Methodsmentioning
confidence: 99%
“…Several researchers have shown that using the traditional scoring method produces some error since the end caps are fixed, however when TES scores are less than 240, corrections have little to no benefit. 21 In addition to TES, a radial plot can be created for each test. An example plot is shown in Fig.…”
Section: Dependent Variablementioning
confidence: 99%
“…16,17,19 It has also been used to test the color rendering properties of different light sources. [20][21][22][23][24] Each of the four series of discs is arranged in a wooden box to which two anchor discs are permanently mounted at either extreme.…”
Section: Apparatusmentioning
confidence: 99%